Screenshot below will hold the question.
![Screenshot below will hold the question class=](https://us-static.z-dn.net/files/dc5/838c22c15b1c756cb80d521a67bcd52d.png)
The equation the completes the proof in step 6 is m<w + m<x = m<x + m<z
In step 4 of the proof, we have the following equation
m<w + m<x = m<y + m<z
In step 5, we have
m<x = m<y
When m<x = m<y is substituted to the equation in step 4, we have:
m<w + m<x = m<x + m<z
Hence, the equation the completes the proof in step 6 is m<w + m<x = m<x + m<z
Read more about mathematical proofs at:
https://brainly.com/question/1788884
#SPJ1